2021
DOI: 10.3390/sym13081492
|View full text |Cite
|
Sign up to set email alerts
|

Study of Temperature Field Distribution in Topographic Bias Tunnel Based on Monitoring Data

Abstract: In recent decades, numerous tunnels have been built in the cold region of China. However, the temperature field of topographically biased tunnels in the monsoon freeze zone has not been sufficiently studied. In this study, we monitored the temperature of the surrounding rock in two topographic bias sections of the Huitougou Tunnel and analyzed the results by fitting them to the monitoring results. The results showed that the temperature of the surrounding rock on both sides after tunnel excavation varied perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The temperature field of surrounding rock of tunnel is the core issue for tunnel construction in cold regions. Especially in topographic bias tunnel, the temperature distribution of surrounding rock is extremely complex, which is affected by various factors such as terrain, burial depth, climate change [28,29]. This study found that the terrain slope angle significantly affect the distribution pattern of the surrounding rock temperature field, causing the temperature field to deflect toward the shallow buried side and changing the freezing depth of the surrounding rock.…”
Section: Influence Of Overburden Thickness On Temperature Fieldmentioning
confidence: 90%
“…The temperature field of surrounding rock of tunnel is the core issue for tunnel construction in cold regions. Especially in topographic bias tunnel, the temperature distribution of surrounding rock is extremely complex, which is affected by various factors such as terrain, burial depth, climate change [28,29]. This study found that the terrain slope angle significantly affect the distribution pattern of the surrounding rock temperature field, causing the temperature field to deflect toward the shallow buried side and changing the freezing depth of the surrounding rock.…”
Section: Influence Of Overburden Thickness On Temperature Fieldmentioning
confidence: 90%